Effect of Cognitive Rehabilitation on Reduction of Attention Bias to Frightful Stimuli in Adolescents with Post-Traumatic Stress Disorder - T. Alsafi; V. Nejati; N.A. Sarhan; M. Maghsudloo (Afarand Scholarly Publishing Institute, 2014)
Aims: Post-traumatic stress disorder is one of the anxiety disorders which is occured in response to total panic in the disaster that threaten the life of the person. The aim of present study was to investigate the effect of cognitive rehabilitation on attention bias to frightful stimulus in people with post-traumatic stress disorder symptoms.  Materials & Methods: in this quasi-experimental study in 2013, 15 Iraqi teenagers with symptoms of post-traumatic stress disorder with age range of 15 to 19 years were selected by random accessible sampling method. The sample group was subjected to 12 sessions of cognitive rehabilitation program. To investigate the effect of cognitive rehabilitation program dot probe test was used. Results were analyzed using independent T-test. Findings: Adolescents with post-traumatic stress disorder after cognitive rehabilitation program, showed significant difference in reaction time (p=0.001), but no significant differences were observed in the number of related and unrelated correct responses, before and after the intervention. Conclusion: Cognitive rehabilitation is an effective way to reduce attention bias to frightful stimuli in people with post-trauma